Laparoscopic para-aortic lymphadenectomy for metastatic colon cancer in a patient with left-sided inferior vena cava: a case report - Efstathios Kotidis; Elissavet Anestiadou; Aikaterini Karamitsou; Georgios Gemousakakis; Orestis Ioannidis; Stefanos Bitsianis; Savvas Symeonidis; Nikolaos Ouzounidis; Odysseas Lomvardeas; Stamatios Aggelopoulos (Folia Medica, 2023)
Transposition of inferior vena cava, or, left-sided inferior vena cava (LS-IVC) is a rare clinical entity, in which the inferior vena cava ascends along the left side of the abdominal aorta. Literature contains mainly clinical case reports. Although it is usually not associated with clinical symptomatology, this anomaly should be detected during preoperative planning to avoid iatrogenic injuries intraoperatively. We present a case of left-sided inferior vena cava encountered during laparoscopic lymphadenectomy in a 45-year-old man with previous laparoscopic hemicolectomy due to colon adenocarcinoma. Preoperative CT abdomen revealed the left-sided location of infrarenal IVC and laparoscopic trans-peritoneal aortic lymphadenectomy was decided. Intraoperatively, transposition of inferior vena cava was confirmed in accordance with the CT findings. Resection of lymph node block was conducted with no complications and with minimal blood loss. The postoperative course was uneventful, and the patient was discharged from the hospital the day following surgery. In conclusion, transposition of the inferior vena cava, although rare, constitutes an anatomical variant that should be identified preoperatively to decrease intraoperative risks. Several anatomical variants have been associated with left-sided inferior vena cava.